A pilot study to compare the detection of HPV-16 biomarkers in salivary oral rinses with tumour p16INK4a expression in head and neck squamous cell carcinoma patients. Issue 1 (December 2016) - Chai, Ryan; Lim, Yenkai; Frazer, Ian; Wan, Yunxia; Perry, Christopher; Jones, Lee; Lambie, Duncan; Punyadeera, Chamindie
Abstract Background Human papilloma virus-16 (HPV-16) infection is a major risk factor for a subset of head and neck squamous cell carcinoma (HNSCC), in particular oropharyngeal squamous cell carcinoma (OPSCC). Current techniques for assessing the HPV-16 status in HNSCC include the detection of HPV-16 DNA and p16INK4a expression in tumor tissues. When tumors originate from hidden anatomical sites, this method can be challenging. A non-invasive and cost-effective alternative to biopsy is therefore desirable for HPV-16 detection especially within a community setting to screen at-risk individuals. Methods The present study compared detection of HPV-16 DNA and RNA in salivary oral rinses with tumor p16INK4a status, in 82 HNSCC patients using end-point and quantitative polymerase chain reaction (PCR). Results Of 42 patients with p16INK4a -positive tumours, 39 (sensitivity = 92.9 %, PPV = 100 % and NPV = 93 %) had oral rinse samples with detectable HPV-16 DNA, using end-point and quantitative PCR. No HPV-16 DNA was detected in oral rinse samples from 40 patients with p16INK4a negative tumours, yielding a test specificity of 100 %. For patients with p16INK4a positive tumours, HPV-16 mRNA was detected using end-point reverse transcription PCR (RT-PCR) in 24/40 (sensitivity = 60 %, PPV = 100 % and NPV = 71 %), and using quantitative RT-PCR in 22/40 (sensitivity = 55 %, PPV = 100 % and NPV = 69 %). No HPV-16 mRNA was detected in oral rinse samples from the p16INK4a -negative patients, yielding a specificity of 100 %. Conclusions We demonstrate that the detection of HPV-16 DNA in salivary oral rinse is indicative of HPV status in HNSCC patients and can potentially be used as a diagnostic tool in addition to the current methods.